Novel QTL and Meta-QTL Mapping for Major Quality Traits in Soybean - Chen, Heng; Pan, Xiangwen; Wang, Feifei; Liu, Changkai; Wang, Xue; Li, Yansheng; Zhang, Qiuying (Frontiers in Plant Science, 2021)
Isoflavone, protein and oil are the most important quality traits in soybean. Since these quality traits are typically quantitative traits, quantitative trait locus (QTL) mapping has been an efficient way to clarify the complex and unclear genetic background of them. However, the low-density genetic map and the absence of QTL integration limited the accurate and efficient QTL mapping in previous researches. This paper adopted a recombinant inbred lines (RIL) population derived from ‘Zhongdou27’and ‘Hefeng25’ and high-density linkage map based on whole genome resequencing to map novel QTL; and used meta-analysis methods to integrate the stable and consentaneous QTL. The candidate genes were obtained from gene functional annotation and expression analysis based on the public database. A total of 41 QTL with high logarithm of odd scores were identified through composite interval mapping (CIM) including 38 novel QTL and 2 Stable QTL. A total of 660 candidate genes were predicted according to the results of gene annotation and public transcriptome data. A total of 212 meta-QTL containing 122 stable and consentaneous QTL were mapped based on 1034 QTL collected from previous studies. For the first-time, 70 meta-QTL associated with isoflavones were mapped in this study. Meanwhile, 69 and 73 meta-QTL respectively related to oil and protein were obtained as well. The results promote the understandings on the biosynthesis and regulation of isoflavones, protein and oil at molecular level, and facilitate the construction of molecular modular for great quality traits in soybean.